2018
DOI: 10.1016/j.physa.2018.06.103
|View full text |Cite
|
Sign up to set email alerts
|

Lee–Yang zeros and two-time spin correlation function

Abstract: The two-time correlation function for probe spin interacting with spin system (bath) is studied. We show that zeros of this function correspond to zeros of partition function of spin system in complex magnetic field. The obtained relation gives new possibility to observe the Lee-Yang zeros experimentally. Namely, we show that measuring of the time dependence of correlation function allows direct experimental observation of the Lee-Yang zeros.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…These ideas now form the theoretical basis of phase transitions in interacting many-body systems. However, while partition function zeros for a long time were considered a purely theoretical concept, recent works have shown that they can also be determined experimentally [35][36][37][38][39][40][41][42][43].…”
Section: A the Ising Model And Lee-yang Zerosmentioning
confidence: 99%
See 1 more Smart Citation
“…These ideas now form the theoretical basis of phase transitions in interacting many-body systems. However, while partition function zeros for a long time were considered a purely theoretical concept, recent works have shown that they can also be determined experimentally [35][36][37][38][39][40][41][42][43].…”
Section: A the Ising Model And Lee-yang Zerosmentioning
confidence: 99%
“…In addition to these theoretical developments, partition function zeros have been determined in several recent experiments [35][36][37][38][39] and additional proposals for their detection have been developed [40][41][42][43]. In the approach that we follow here, the partition function zeros are extracted from the fluctuations of the thermodynamic observable that couples to the control parameter, for instance, magnetization and magnetic field, or energy and inverse temperature [9,32,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…However, while partition function zeros for a long time were considered a purely theoretical concept, recent works have shown that they can also be determined experimentally. [35][36][37][38][39][40][41][42][43]…”
Section: Lee-yang Theory a The Ising Model And Lee-yang Zerosmentioning
confidence: 99%
“…[32][33][34] In addition to these theoretical developments, partition function zeros have been determined in several recent experiments [35][36][37][38][39] and additional proposals for their detection have been developed. [40][41][42][43] In the approach that we follow here, the partition function zeros are extracted from the fluctuations of the thermodynamic observable that couples to the control parameter, for instance, magnetization and magnetic field, or energy and inverse temperature. 9,32,44,45 The scheme is attractive from an experimental point of view since it makes it possible to explore phase transitions by measuring fluctuatuation in small systems, even for systems that are away from criticality.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, partition function zeros were measured using carefully engineered nano-structures involving the precession of interacting molecular spins [17][18][19], Cooper pair tunneling in superconducting devices [20][21][22], or fermionic atoms in driven optical lattices [23]. In parallel with these experiments, several theoretical proposals have been put forward for the detection of partition function zeros [24][25][26][27][28]. These advances motivate a number of questions, which now should be addressed.…”
mentioning
confidence: 99%